2004
DOI: 10.1289/ehp.6701
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction in simultaneous exposure to Streptomyces californicus and Stachybotrys chartarum.

Abstract: The microbial exposure associated with health complaints in moldy houses consists of a heterogeneous group of components, including both living and dead bacteria, fungi, and their metabolites and active compounds. However, little is known about the interactions between different microbes and their metabolites, although the cytotoxicity and inflammatory potential of certain individual microbes have been reported. In this study, we investigated the inflammatory responses of mouse RAW264.7 macrophages after expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 44 publications
0
52
0
1
Order By: Relevance
“…These mixed biofilms, which have also been evidenced with C. albicans (195,289), can be more resistant to antibiotic treatments; for example, the presence of Staphylococcus epidermidis was shown to delay the diffusion of antifungal drugs in mixed Candida-Staphylococcus biofilms (6). Bacterial-fungal associations with potentially detrimental impacts on human health may also occur in moldy houses (170). In these damp environments, actinobacteria frequently cohabit with fungal genera associated with moisture damage, such as Stachybotrys and Aspergillus.…”
Section: Roles In Host Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…These mixed biofilms, which have also been evidenced with C. albicans (195,289), can be more resistant to antibiotic treatments; for example, the presence of Staphylococcus epidermidis was shown to delay the diffusion of antifungal drugs in mixed Candida-Staphylococcus biofilms (6). Bacterial-fungal associations with potentially detrimental impacts on human health may also occur in moldy houses (170). In these damp environments, actinobacteria frequently cohabit with fungal genera associated with moisture damage, such as Stachybotrys and Aspergillus.…”
Section: Roles In Host Health and Diseasementioning
confidence: 99%
“…In these damp environments, actinobacteria frequently cohabit with fungal genera associated with moisture damage, such as Stachybotrys and Aspergillus. Research evaluating the impact of such BFIs in cell lines indicates a significant potential for synergistic effects between these bacteria and fungi on cytotoxicity and mammalian inflammatory responses (170,267,304,305). While mixed bacterial-fungal communities have been shown to have detrimental effects on human health, to our knowledge, there have been no reports describing the roles of intrahyphal bacteria in fungal infections of humans.…”
Section: Roles In Host Health and Diseasementioning
confidence: 99%
“…Several microbial indicators have been suggested to associate with moisture damage and/or health complaints (13,27,33,39,46,58), yet a consensus regarding their causative role in relation to the health effects is lacking. The potential harmfulness of microbial contamination is suggested to be dependent on the species content and concurrently occurring species combinations, as well as on the material and growth conditions in which the microbial proliferation occurred (19,31,53,59,71).…”
mentioning
confidence: 99%
“…The skin or gastrointestinal tract may become infested with mold and fungal substrates, and inhalation of fungal units and spore-borne toxins are important sources of exposure [7]. Nevertheless, health problems caused by inhaled mycotoxins tend to be more serious than those caused by mycotoxins absorbed via the digestive tract or skin [13][14][15][16]. Creasia et al [25] showed that mycotoxins can be 10 times more toxic through inhalation than by systemic administration in mice.…”
Section: Overall Risks In Damp and Moldy Indoor Environmentsmentioning
confidence: 99%
“…Other groups at risk, such as the elderly [9] and young children [10,11], have been noted for their susceptibility to the harmful effects of indoor air and fungi. Both direct fungal infection (mycosis) [7] and toxigenic effects of fungal mycotoxins have been reported [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%